THE INFLUENCE OF EMPLOYEE WORK CULTURE ON ELECTION ADMINISTRATION MANAGEMENT IN THE GENERAL ELECTION COMMISSION OF PASAMAN REGENCY: (Studies on Voter Data Updating Stages and Voter List Compilation in 2019) - Putri, Rahmi Esa; Frinaldi, Aldri (Transpublika Publisher, 2022)
This research aims to see the influence of work culture on the management of election administration in the General Election Commission of Pasaman Regency. In this study, the authors conducted a study on the stages of updating voter data and compiling voter lists. The method used is quantitative methods. This research focused on the stages of compiling the voter list and updating the voter list. The study populations were all employees who were members of the Election Commission General Pasaman District, the sample was taken by total sampling, namely employees who were civil servants and non civil servants, as many as 36 people. Data collection techniques in this study the author obtained from a questionnaire, the statement items in the research questionnaire were made using scale measurement Likert. The data obtained were then analyzed by using technique regression linear simple. The results showed that there is a significant influence between work culture variables on the management of election administration, with an R squer value of 69.9% and a significant value of 0.000 which indicates a significant effect, and the T test with a value of 0.000 so that it can be concluded that Ha is accepted and Ho rejected, and for each indicator from work culture, namely leadership, appearance, time awareness, appreciation and recognition, as well as values and beliefs also affect election administration management with a significant value of 0.000 which means work culture has a significant effect on administrative management.